Mapping the Intersection of Organizational Justice and Sustainability Development in Asian Higher Education: A Bibliometric Perspective - Nazaria, Md. Aris; Muhammad Harith Hakimi, Razman (Nova Science Publisher, 2026)
The pursuit of sustainability has become a defining priority in higher education institutions across Asia. Within this shift, organizational justice, covering fairness in decision-making, resource distribution, and interpersonal treatment, emerges as a critical yet often overlooked factor in advancing sustainable practices. This chapter explores the intersection of sustainability and organizational justice in Asian higher education through a bibliometric analysis of academic literature published between 2014 and 2024. Using Harzing’s Publish or Perish and VOSviewer, 92 relevant publications were systematically selected following PRISMA guidelines. Findings reveal a rapidly growing field, primarily driven by research from China, India, and Indonesia, rooted in social sciences and management disciplines. The bibliometric analysis highlights regional and disciplinary fragmentation, with limited cross-national collaboration. Meanwhile, thematic mapping identifies equity as a central bridge linking micro-level justice issues with macro-level sustainability agendas. This chapter highlights the crucial role of equity as an integrative framework, positioning Asian higher education as both an innovative scholarly space and a catalyst for social and environmental transformation. The insights provided aim to inform future research, policymaking, and institutional practices by clarifying the current knowledge landscape and identifying areas for further exploration.